Report
1941-11 038-0024-012 14 For these the Committee finds jobs wherever possible. Help and advice is also given in individual cases. Recently it was possible to save one of these girls from eventual blindness by arranging treatment at a hospital and obtaining the money for special glasses. Our present satisfactory financial position — where the monthly expenditure is a little more than covered by the monthly donations we receive — is largely due to the forethought and personal efforts of the general secretary, Mrs. Miller, who by drastic reorganisation of the office, and careful husbanding of its greatly reduced resources, has managed to obtain a final settlement of outstanding debts; and with a skilfully-run appeal is slowly building up a reserve to meet our incalculable future responsibilities. In this work she has been most ably assisted by the devoted help of our accountant, Mr. Morris, whose whole life was spent in Spain until the Civil War, and a small staff of young Spaniards and Basques employed at Headquarters. So the varied responsibilities though reduced still remain, and money is urgently required to enable the small staff at Headquarters who play such an important part in the lives of these Spaniards who remain — whether adult or child — to continue their work. Space alone prevents us from giving full details of those many friends who have helped, and are still helping, but we should like to take this opportunity to thank the many sections of the Trade Union movement, Co-operative Societies and Guilds, to the Labour, Liberal, Church and University Groups, and many working men's clubs and book clubs. The Save the Children Fund, The International Commission for War Refugees in Great Britain, The Society of Friends, the Mennonite Central Committee of U.S.A. and Canada, Dr. Barnardo's Homes, The British Red Cross Society, The Miners' Federation of Great Britain, The South Wales Miners' Federation, The Civil Service Clerical Association, The Women's Voluntary Service, The Workers' Educational Association, The Spanish Medical Aid, The National Council of Social Service and Citizen's Advice Bureau, The International Labour Branch of the Ministry of Labour and National Service, The Christian Science War Relief Fund, and The Salvation Army. To the many Spanish Groups, and the Basque Delegation, and our grateful acknowledgment of the courtesy of Messrs. Chubb & Co., for the loan of a safe for so long a period. November, 1941. 292/946/38/24(XII)